PERAN KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI LEMBAGA PENJAMIN SIMPANAN SURABAYA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Susanti, Ratna Koba (Growth, 2025)
The purpose of this study is to obtain empirical evidence on the influence of leadership and motivation on performance and job satisfaction as intervening variables. Using the quantitative approach Partial Least Square (PLS). The results show that leadership has a significant positive effect on job satisfaction. Motivation has a significant positive effect on job satisfaction. Leadership has a positive but insignificant effect on employee performance. Motivation has a significant positive effect on employee performance. Job satisfaction has a positive but insignificant effect on employee performance. Leadership has a positive but insignificant effect on employee performance through job satisfaction. Motivation has a positive but insignificant effect on employee performance through job satisfaction.